The Reality of Emirati Women’s Political Participation in the Federal National Council - Alzaabi, Mariam; Yaiche, Ouassila (Al-Adab Journal, 2025)
Women’s representation in parliament happens to be one of the most vital forms of their political participation. Nevertheless, the level of progress being achieved in this arena is still slow regionally and internationally. The United Arab Emirates (UAE) is a young Arab state that was established in 1971, yet it went from zero representation of women in the parliament to equal representation in less than five decades. This study addresses the reality of Emirati women’s political participation in the Federal National Council (FNC), as voters, candidates, and members. Using descriptive analysis, it highlights the different stages the FNC went through and the female presence in each stage. The study concluded that Emirati leadership adopted a gradual approach in involving Emirati women in parliamentary life. By having the opportunity and the competence, Emirati women were able to take on the initiative and became FNC members for the first time in 2007. In 2015, a female was voted in as a chaired of the FNC. And since 2019, Emirati women have been equally represented in the FNC, due to a quota system implemented by the government.